Service quality and influencing factor on consumer purchase intention of online ticketing: an empirical study in Iran - Nikhashemi, Seyed Rajab; Haque, A. K. M. Ahasanul; Yasmin, Farzana; Khatibi, Ali (Society of Business and Management Dynamics, 2012)
This study gives a report on e-service quality and consumer purchase intention towards online ticketing. In this research, the reasons why some people remain committed to the traditional method of purchasing materials while others have embraced the use of online channels were investigated. The outcome of this study is a comprehensively integrated framework that can be utilized by the policy makers and business enterprises to understand significant relationships among dimensions of e-service quality, perceive of usability, perceived risk and internet knowledge. Also, this research considered how price perception and online trust can be utilized in understanding the consumers’ purchase intention towards online ticketing. In addition, another factor which has made this study very sophisticated is the e-service quality aspect which has significant effect on consumer purchase intention behavior to have online purchase. However, further research is needed to examine these factors in Iran with additional samples before generalization can be made. Furthermore, it is also necessary to review consumer purchasing behavior in taking decision to use internet as means of purchasing online rather than the traditional way.